A gynandromorph of Xylocopa augusti and an unusual record of X. iris from Brazil (Hymenoptera: Apidae: Xylocopini) - Lucia, Mariano (2015)
We describe and illustrate for the first time a mixed gynandromorph of Xylocopa(Neoxylocopa) augusti Lepeletier de Saint Fargeau from Buenos Aires, Argentina. Also, we document and discuss a historical specimen of the Old World carpenter bee X. (Copoxyla) iris (Christ) possibly collected in Brazil.